Isolation of oceanic and coastal populations of the harvested mother-of-pearl shell Tectus niloticus in the Kimberley - Berry, O.; Richards, Zoe; Moore, G.; Hernawan, U. (Western Australian Marine Science Institution, 2017)
This report focuses on “trochus” or “mother of pearl shell” Tectus niloticus, which is a large harvested gastropod mollusc common on intertidal reefs in the Kimberley and the wider Indo-Pacific. This species was selected as a model for a study of connectivity in molluscs because it has a short larval life-history (3-5 days), which is typical of species whose recruitment is primarily local and they are prone to over-harvest. Over-harvest of T. niloticus has been documented throughout its range, and it's been argued that placement of reserves adjacent to harvested regions would be an effective way to sustain the species. However, the unique complexity and power of the Kimberley hydrodynamic environment potentially enlarges the scale of recruitment and/or creates spatially complex dynamics that may be relevant to harvest management in the region.